High-risk US International Travelers Seeking Pretravel Consultation During the COVID-19 Pandemic. (3rd August 2022) - Hyle, Emily P; Le, Mylinh H; Rao, Sowmya R; Mulroy, Nora M; Walker, Allison T; Ryan, Edward T; LaRocque, Regina C
Abstract: Background: To assess the implications of coronavirus disease 2019 (COVID-19)–related travel disruptions, we compared demographics and travel-related circumstances of US travelers seeking pretravel consultation regarding international travel at US Global TravEpiNet (GTEN) sites before and after the initiation of COVID-19 travel warnings. Methods: We analyzed data in the GTEN database regarding traveler demographics and travel-related circumstances with standard questionnaires in the pre-COVID-19 period (January–December 2019) and the COVID-19 period (April 2020–March 2021), excluding travelers from January to March 2020. We conducted descriptive analyses of differences in demographics, travel-related circumstances, routine and travel-related vaccinations, and medications. Results: Compared with 16 903 consultations in the pre-COVID-19 period, only 1564 consultations were recorded at GTEN sites during the COVID-19 period (90% reduction), with a greater proportion of travelers visiting friends and relatives (501/1564 [32%] vs 1525/16 903 [9%]), individuals traveling for >28 days (824/1564 [53%] vs 2522/16 903 [15%]), young children (6 mo–<6 y: 168/1564 [11%] vs 500/16 903 [3%]), and individuals traveling to Africa (1084/1564 [69%] vs 8049/16 903 [48%]). A smaller percentage of vaccine-eligible travelers received vaccines at pretravel consultations during the COVID-19 period than before, except for yellow fever and Japanese encephalitis vaccinations. Conclusions: Compared with the pre-COVID-19 period, a greater proportion of travelers during the COVID- 19 period were young children, were planning to visit friends and relatives, were traveling for >28 days, or were traveling to Africa, which are circumstances that contribute to high risk for travel-related infections. Fewer vaccine-eligible travelers were administered travel-related vaccines at pretravel consultations. Counseling and vaccination focused on high-risk international travelers must be prioritized during the COVID-19 pandemic. Abstract : The demographics of US international travelers seen for pre-travel health consultation changed during the COVID-19 pandemic. Compared with pre-COVID-19, a greater percentage of travelers were planning to visit friends and relatives or were traveling for extended periods.